(untitled) (Scientific journal of the Fergana State University, 2023)
Linguistic units representing product and brand names - well-known names - are called by linguists in scientific sources with terms such as pragmonim, tovaronim, pragmatonim. Ergonims denoting company, organization, enterprise names were analyzed in several groups, brand meaning of the product or service was explained, pragmatonyms were used to classify, describe, compare and illuminate the distinguishing elements and functions of popular brand names. the place of the phenomenon in the language system was determined.The brand includes examples such as the brand name, logo, slogan, shape, color, tone and tone, ifor, taste, and movement. Social, psychological and linguistic factors were found to be important in brand name selection and promotion. Pragmatonyms have been shown to perform distinctive, informative, "protective", guarantee, and psychological functions.